(untitled) (Journal of Economic Research & Business Administration, 2015)
This paper reports introduction of IFRS promotes conducting tax accounting in the country and to transition of the Kazakhstan economy to qualitatively new level of development when the favorable investment climate, transparency of financial statements, openness, reliability of a financial position and results of activity of the companies becomes the main values. In case of application of IFRS there are new financial instruments, in assets investments and obligations of the companies control over which is provided with direct participation in the capital are reflected. Besides, Kazakhstan will join WTO soon in which all participating countries accounting reports are kept on IFRS.One of the major problems connected with IFRS, lack of enough of qualified personnel still is. And it is a question not only of reporting preparation, but also of understanding and its use. The chamber of auditors of Kazakhstan in 2006 after numerous and long negotiations made the decision on development of the unique program of certification of accountants and auditors.